OVERCOMING DIFFICULTIES IN COMPREHENDING LISTENING SKILL OF 11TH GRADE PUPILS - Xoshimova, Diyora Azamjon qizi (Educational Research in Universal Sciences, 2023)
One of the most essential skills in English language learning is listening. When students listen to English audios in classes, they face a lot of challenges. Pupils have critical issues in listening comprehension because some school teachers pay more attention to writing, vocabulary and reading tasks. Many course books do not include listening materials and most tutors do not pay attention to this significant skill in the English classes. In this research paper, the researcher reviewed the terms listening, the strategies of listening, difficulties in listening and listening comprehension. The review of some topic based literature and some other researches indicated that when teachers are aware of exact difficulties and problems in listening task of their students, they can help the students to improve effective listening strategies and to try some possible solutions to develop their listening understanding abilities.